A fast and powerful release mechanism based on pulse heating of shape memory wires. (23rd August 2017) - Malka, Yoav; Shilo, Doron
Abstract: This article presents a novel actuator and a new concept for a release mechanism that are especially useful in applications that require fast motion of large masses over long distances. The actuator is based on ultra-fast pulse heating of NiTi wires, which provide a unique combination of large work per volume, short response time and enhanced energy efficiency. The release mechanism utilizes the fast and powerful actuator to form conditions in which the latch (safety pin) moves faster than the deployed device. As a result, the contact between these two masses is disconnected and the resulting friction forces are decreased to approximately zero. The actuator and release mechanism address the two major drawbacks of conventional shape memory alloy (SMA) actuators: slow actuation time and low energy efficiency. Using a dedicated setup, the experimental results validate the disconnection between the masses and map the effects of several variables on the performance of the actuator and release mechanism. In particular, we map the energetic efficiency and find the optimal operating conditions for a successful release using a minimal amount of input energy. At the optimal conditions, the actuator response time and the consumed input energy are smaller by an order of magnitude with respect to performances of previous SMA-based release mechanisms with comparable requirements.